PWE-125 Transjugular intrahepatic portosystemic shunt insertion is safe and effective in district general hospital setting. (22nd June 2015) - Domanski, A; Bent, C; Beckett, D; Oakes, J; Shawyer, A; Williams, E; Al-Shamma, S
Abstract : Introduction: Transjugular intrahepatic portosystemic shunt (TIPS) insertion is a recognised rescue treatment for uncontrollable bleeding due to portal hypertension and can also be used for refractory ascites. TIPS is usually performed by interventional radiology (IR) and normally in a 'teaching' hospital setting. Reported mortality rates are 27–50%. 1 At our institution, a large DGH, a 24-hour IR-led TIPS service has been established since 2007. The aim of this study was to assess technical success, complications and mortality associated with TIPS. Method: Using a TIPS database, we conducted analysis of patients who had undergone a TIPS procedure between 2007 and 2014. Data collected included demographics, indication, success rate, short and long term complications and mortality. A total of 32 patients were identified and case notes were available for 25. Results: Of the 25 patients identified, 18 (72%) were male. The mean age was 48.4 (25–73.) Child–s score was A in 5 (20%), B in 11 (44%) and C in 9 (36%). Six patients (24%) had a MELD <12, 11 (44%) 12–18 and 8 (32%) >18. The commonest underlying aetiology was alcohol in 12 (48%), alcohol and HCV in 6 (24%) and NASH in 3 (12%). The commonest indication was uncontrolled/recurrent bleeding in 18 (60%), gastric varices in 3 (12%) and refractory ascites in 4 (16%). Six (24%) had undergone OGD once before TIPS, 9 (36%) had 2 OGDs and 4 (16%) had 3. Technical success was achieved in 23 (92%). Two patients underwent further TIPS refashioning. There was one TIPS thrombosis soon after insertion. Of 21 patients receiving TIPS for bleeding, 18 (86%) required no further endoscopies. Three patients rebled (14%) requiring repeated endoscopy. There were no significant procedure-related complications. Severe refractory hepatic encephalopathy occurred in only 1 patient (4%). The 30-day mortality was 28% (7 patients) and 1-year mortality was 44% (11). Most deaths occurred in patients with Child–s C disease (4 patients at 30-days and 7 at 1-year) with no 30-day mortality in Child–s A. Three patients aged over 65 underwent TIPS, 2 died within 30 days (Child–s B) and 1 within 1 year (Child–s A.) All patients who died had a MELD score >15. The commonest cause of death was either rebleeding or multiorgan failure. Conclusion: TIPS can be safely and effectively performed in a DGH setting with success, complication and mortality rates comparable to larger 'teaching' centres. As with other studies, severity of liver disease and age are important predictors of mortality. Disclosure of interest: None Declared. Reference: Loffroy R, et al . Transjugular intrahepatic portosystemic shunt for the management of acute variceal hemorrhage. World J Gastro . 2013 October 7;19(37):6131-6143